PSO-backstepping controller of a grid connected DFIG based wind turbine - Salmi Hassan; Badri Abdelmajid; Zegrari Mourad; Sahel Aicha; Baghdad Abdenaceur (Institute of Advanced Engineering and Science, 2020)
The paper demonstrates the feasibility of an optimal backstepping controller for doubly fed induction generator based wind turbine (DFIG). The main purpose is the extract of maximum energy and the control of active and reactive power exchanged between the generator and electrical grid in presence of uncertainty. The maximum energy is obtained by applying an algorithm based on artificial bee colony approach. Particle swarm optimization is used to select optimal value of backstepping’s parameters. The simulation is carried out on 2.4 MW DFIG based wind turbine system. The optimized performance of the proposed control technique under uncertainty parameters is established by simulation results.